Dialogue therapy for couples and real dialogue for opposing sides : methods based on psychoanalysis and mindfulness - Pieniadz, Jean, 1956-; Young-Eisendrath, Polly, 1947- (New York, NY : Routledge, 2022)
"A clear, cogent, and comprehensive account of the rationale and methods of Dialogue Therapy and Real Dialogue, this volume introduces models of facilitated dialogue designed specifically to end polarization. This book offers a straightforward and comprehensive encounter with some of the most effective theories and methods to facilitate dialogue and disrupt deadening power struggles between life partners, grown children and parents, siblings, co-workers, and others whose conflicts have led to harmful polarizations. The book is based on ideas and relational models from mindfulness and psychoanalysis that have not been applied in this unique way before. This melding of mindfulness (containment, concentration, equanimity, maintaining a "mindful gap") with the psychoanalytic understanding of projection and projective identification (the "hijacking" of our subjective experiences) creates much more than light at the end of the tunnel. It engenders the acceptance of another that leads to love and insight, based on the Crecognition and acknowledgement of our autonomy and our common humanity in the midst of conflict. This book introduces a new, revolutionary model for couple therapists, life coaches, group facilitators, and leaders to open a mindful space that increases witnessing capacities in the midst of emotional conflict, without imposing goals of agreement, reconciliation or compromise"--
Keywords: Couples therapy; Dialogue; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health